Behavior of welded joints on the roof truss of KOJK Office using LISA V.8 FEA - Aco Wahyudi Efendi (Journal of Metallurgical Engineering and Processing Technology, 2024)
Welded joints play a crucial role in the structural integrity of buildings, particularly in supporting heavy loads and resisting various forces such as wind, seismic, and gravitational loads. This research was carried out by identifying the stresses that occur in the welded joints of the truss trusses of the roof of the KOJK Central Java building, with initial analysis conditions of rigid and stiff connections, and second conditions with conditions that occur according to field findings, where the joints are non-standard and there are several holes due to welding. not perfect. Modeling analysis uses Finite Element Analisys software, namely LISA V.8 FEA (License), to obtain the stress behavior that occurs in the roof truss elements of KOJK Central Java. From the results of analysis and modeling by making two conditions, namely the condition of welding joints according to standards and welding joints under field conditions. The stress ratio at the weld joint is 1.351 and the stress ratio at the truss pull rod is 1.054.